2015
DOI: 10.1016/j.jmb.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Protein SLP-76 Primes PLCγ1 for Activation by ITK-Mediated Phosphorylation

Abstract: Activation of the phospholipase, PLCγ1, is critical for proper T cell signaling following antigen receptor engagement. In T cells, the Tec family kinase, ITK, phosphorylates PLCγ1 at tyrosine 783 (Y783) leading to activation of phospholipase function and subsequent production of the second messengers IP3 and DAG. In this work we demonstrate that PLCγ1 can be primed for ITK mediated phosphorylation on Y783 by a specific region of the adaptor protein, SLP-76. The SLP-76 phosphotyrosine containing sequence, pY173… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…However, we have not addressed the subsequent recruitment to SLP-76 of Nck, Vav, and Itk. In this system Nck and Vav are thought to have a scaffolding function, and Itk, a member of the Tec family of PTKs, is required to phosphorylate PLC-γ1 on tyrosine 783, an event needed for the activation of the enzyme (39,40). In addition to the requirement for these binding events for PLC-γ1 activation, it is possible that these additional molecules might affect the interaction and dynamics of the fourmolecule complex that is the subject of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have not addressed the subsequent recruitment to SLP-76 of Nck, Vav, and Itk. In this system Nck and Vav are thought to have a scaffolding function, and Itk, a member of the Tec family of PTKs, is required to phosphorylate PLC-γ1 on tyrosine 783, an event needed for the activation of the enzyme (39,40). In addition to the requirement for these binding events for PLC-γ1 activation, it is possible that these additional molecules might affect the interaction and dynamics of the fourmolecule complex that is the subject of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The new report from Devkota et al addresses highly related aspects of PLCγ1 regulation but in a different signalling context [5]. Significantly, these researchers used heteronuclear NMR spectroscopy to provide evidence that is consistent with the idea that the canonical cSH2 binding site is occupied in cis by the adjacent Tyr783-containing linker segment, even in the absence of phosphorylation.…”
mentioning
confidence: 92%
“…As that work has progressed and inexorably expanded away from modular domains towards multiprotein signalling assemblies, it has become clear that the simple plug-in-socket picture fails to completely capture a much more nuanced picture for the regulatory role that SH2 domains play, both in three dimensions (structure) and the fourth, time dimension (function) [4]. It is in that vein that the work of Devkota et al, reported in this issue [5], describes aspects of the interaction between the C-terminal SH2 domain of phosphatidylinositol PLCγ1 (phospholipase C γ 1) and the scaffolding protein SLP-76 (SH2 domaincontaining leukocyte protein, 76 kDa).Phospholipases C (PLCs) act to convert membranebound phosphatidylinositol-4,5-bisphosphate PIP 2 phospholipids into the second messengers diacylglycerol and inositol-1,4,5-trisphosphate IP 3 that effect activation of protein kinases C and calcium signalling, respectively [6][7][8]. In mammals, there are six families of PLCs (β, γ, δ, ε, η and ζ).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In the PLC γ resting state, the extent to which the cSH2 domain is “available” for contact with the enzyme core and upstream agonists is unclear. In this context, the binding status of the cSH2 C-terminus, which is equivalent to the cSH2-SH3 linker and harbors the Tyr771, Tyr775, and Tyr783 phosphorylation sites, plays a particular role; recent studies proposed that Tyr783 phosphorylation by ITK kinase and Tyr771 phosphorylation by FGFR2 kinase would occur because of an enhancement of C-terminus availability ( 12 , 16 ). Although tandem SH2 crystal structures suggest that the cSH2 C-terminus might indeed be unbound in the nonphosphorylated state ( 10 ), a recent NMR study comparing constructs with and without an unmodified C-terminal extension suggested that the C-terminus is bound even in the nonphosphorylated state ( 16 ).…”
Section: Introductionmentioning
confidence: 99%